Does R&D Stimulate Firm’s Efficiency in the Indonesian Manufacturing Sector? - Yasin, Mohammad Zeqi (Jurnal Ikatan Sarjana Ekonomi Indonesia, 2023)
The impact of research and development (R&D) spending has been shown significantly in promoting country’s economic growth and productivity. Hence, we examine the research question by employing Indonesian manufacturing firm-level dataset in the years of 2017–2019 and by using Stochastic Frontier Analysis (SFA) to reveal whether heterogeneous firm’s R&D spending contributes to the efficiency performance of the company. The finding reveals the robust positive effect of R&D spending to the efficiency performance, which implies that firms allocating more R&D spending will perform better efficiency due to, for example, managerial expertise improvements. An interesting finding is shown by the interaction model for which larger R&D allocated by foreign firm will boost better efficiency than that allocated by domestic firms, supporting prior arguments that foreign firm can be the driver of innovation as they are more likely to be closer to the world technology frontier. Several policy implications are suggested such as in-house R&D program to encourage human capital development and tax incentive to avoid market rivalry with foreign firms.